RNase T is responsible for the end-turnover of tRNA in Escherichia coli. - Deutscher, M P (1985)
A mutant strain deficient in RNase T was isolated and used to study the role of this enzyme in Escherichia coli. Strains lacking as much as 70% of RNase T activity, alone or in combination with the absence of other RNases, display normal growth properties. However, in cca strains, which lack tRNA nucleotidyltransferase, RNase T-deficient derivatives accumulate lower levels of defective tRNA and grow at increased rates compared to their RNase T+ parents. Slow-growing cca strains revert to a faster-growing form that contains less defective tRNA but which is still cca. All of these strains have decreased levels of RNase T. These data indicate that RNase T is responsible for nucleotide removal during the tRNA end-turnover process and that the amount of defective tRNA in cells is determined by the relative levels of RNase T and tRNA nucleotidyltransferase.